2015
DOI: 10.1186/s40064-015-1326-7
|View full text |Cite
|
Sign up to set email alerts
|

Clinical decision upon resection or observation of ocular surface dermoid lesions with the visual axis unaffected in pediatric patients

Abstract: Ocular surface or epibulbar dermoid lesions may present as limbal dermoids at the corneal limbus or dermolipomas in the conjunctival fornix. The purpose of this study is to review clinical features of ocular surface dermoids (grade I), with the visual axis unaffected, in pediatric patients, in order to find key features for making clinical decision, either resection or observation. The study involved 13 consecutive patients with limbal dermoids or fornix dermolipomas which did not affect the visual axis, seen … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…Visual acuity testing at school age is mainly aimed at detecting refractive errors, especially myopia, which is at a higher rate in Japan [ 20 ]. The vision-screening program in the earlier years of life is also intended to detect rare congenital diseases such as congenital cataract [ 21 ], ectopia lentis [ 22 ], ocular surface dermoid lesions [ 23 ], congenital ptosis [ 24 ], and congenital superior oblique muscle palsy [ 25 ]. These rare diseases are frequently associated with refractive errors that lead to the development of amblyopia.…”
Section: Discussionmentioning
confidence: 99%
“…Visual acuity testing at school age is mainly aimed at detecting refractive errors, especially myopia, which is at a higher rate in Japan [ 20 ]. The vision-screening program in the earlier years of life is also intended to detect rare congenital diseases such as congenital cataract [ 21 ], ectopia lentis [ 22 ], ocular surface dermoid lesions [ 23 ], congenital ptosis [ 24 ], and congenital superior oblique muscle palsy [ 25 ]. These rare diseases are frequently associated with refractive errors that lead to the development of amblyopia.…”
Section: Discussionmentioning
confidence: 99%
“…In infants and children, the eyeball and the visual acuity are in the process of growth and development, and general anesthesia is required in pediatric eye surgeries. [10] Considering the tumor size, the tumor growth rate, and the involved areas, the appropriate time and techniques of surgical interventions are still controversy in infants and children. The proper treatment is particularly challenging in young children because of the tendency for a low visual acuity and astigmatism-related amblyopia.…”
Section: Discussionmentioning
confidence: 99%
“…The AM has been used for the reconstruction of the conjunctiva and resulted in a good cosmetic outcome [ 18 , 19 ]. The AM has also been widely used in the reconstruction of corneal surface in several injuries such as neurotrophic ulcers [ 34 , 35 ], persistent epithelial defects, microbial keratitis [ 36 , 37 ], band keratopathy, bullous keratopathy [ 38 , 39 ] and chemical injuries [ 38 , 40 ]. Due to its properties, an AM implant was used in this 12-year-old patient with a recurrent dermoid cyst.…”
Section: Discussionmentioning
confidence: 99%
“…In the study reported by Matsuo, the clinical characteristics of superficial ocular dermoid cysts in paediatric patients [ 40 ] were evaluated in order to offer the best option for a clinical decision-making; either resection or observation of the cyst growth to determine the appropriate time for the excision. In this study we showed the efficacy and safety of the AM implant with MMC application to repair conjunctival defects after removal of the dermoid cyst.…”
Section: Discussionmentioning
confidence: 99%